Endoscopic Transsphenoidal Surgery of Microprolactinomas: A Reappraisal of Cure Rate Based on Radiological Criteria - Micko, Alexander; Vila, Greisa; Höftberger, Romana; Knosp, Engelbert; Wolfsberger, Stefan (Neurosurgery, 2019)
Abstract Background Current standard treatment of microprolactinomas is dopamine agonist therapy. As this drug treatment is lifelong in up to 80% of cases, many patients consult pituitary surgeons regarding a surgical alternative. Objective To identify prognostic criteria for surgical remission, we reviewed outcomes of our series of microprolactinomas treated with endoscopic transsphenoidal surgery, with a special emphasis on magnetic resonance adenoma delineation and position. Methods Our study cohort comprises a single center series of 60 patients operated for histopathologically verified magnetic resonance imaging unequivocally identifiable endosellar microprolactinoma between 2003 and 2017. In 31 patients the adenoma was enclosed by pituitary gland (group ENC), in 29 patients the adenoma was located lateral to the gland adherent to the medial cavernous sinus wall (group LAT). Results After a mean follow-up of 37 mo (range 4-143 mo), remission rate was significantly higher in adenomas enclosed by pituitary gland (group ENC) than adenomas located lateral to the gland (group LAT), with 87% vs 45%, P = .01. Intraoperatively, 4 patients showed signs of invasiveness. Preoperative prolactin levels did not differ between the groups (mean 155 and 187 ng/ml in group ENC and LAT, respectively). A binary logistic regression model revealed that only the radiological criteria applied showed a significant correlation (P = .003) with endocrine remission. CONCLUSION According to our results, remission rate is significantly higher in microprolactinomas enclosed by the pituitary gland. However, the decision for surgery should take into account surgeons experience and possibility of complications.